Occupation during life and risk of dementia in French elderly community residents. Issue 3 (1st September 2001) - Helmer, C; Letenneur, L; Rouch, I; Richard-Harston, S; Barberger-Gateau, P; Fabrigoule, C; Orgogozo, J M; Dartigues, J F
Abstract : OBJECTIVE: To determine whether principal occupation during life is a risk factor for incident Alzheimer's disease, vascular dementia, or dementia with parkinsonism. METHODS: This study was carried out from the PAQUID (Personnes Agées QUID) cohort, an epidemiological study on normal and pathological aging after 65 years in the south west of France. At baseline, 2950 non-demented people living at home were identified and re-examined 1, 3, 5, 8, and 10 years later with identical standardised neurological and neuropsychological measures. Cox proportional hazards models with delayed entry were used, taking age as the time scale and adjusting for sex, education, tobacco, and wine consumption to estimate the risk ratio (RR) of incident dementia, Alzheimer's disease, vascular dementia, and dementia with parkinsonism associated with occupational category. RESULTS: Of the 2950 subjects, 393 became demented, of whom 251 had Alzheimer's disease, 112 had vascular dementia, and 27 had dementia with parkinsonism. The risk of Alzheimer's disease was not related to a given occupation. However the risk of dementia with parkinsonism seemed to be increased in farmers in comparison with professionals and managerials, particularly among women (RR 7.47; 95%CI, 1.80–31.07). CONCLUSION: The data suggest that occupation does not change the risk of Alzheimer's disease, which seems to be more influenced by cognitive abilities in childhood and adolescence than by occupation in adult life. However, being a farmer may increase the risk of dementia with parkinsonism among women; occupation could act by the way of differences in health behaviour or in exposure to environmental factors.